PERANAN LEMBAGA BANTUAN HUKUM DALAM MEMBERIKAN BANTUAN HUKUM KEPADA MASYARAKAT TIDAK MAMPU DITINJAU DARI PUTUSAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2014 - La Ode Sarman; Nasrin Nasrin (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2022)
Indonesia is a state of law. This is in line with the provisions of Article 1 paragraph (3) of the 1945 Constitution of the Unitary State of the Republic of Indonesia which reads that the State of Indonesia is a state of law. Then in article 27 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, it reads